Morphological Changes in the Bone Marrow of the Dogs with Visceral Leishmaniasis - Claudia Momo; Ana Paula Prudente Jacintho; Pamela Rodrigues Reina Moreira; Danísio Prado Munari; Gisele Fabrino Machado; Rosemeri de Oliveira Vasconcelos (Veterinary Medicine International)
The aim of this study was to evaluate the most frequent lesions in the bone marrow of dogs naturally infected by Leishmania (Leishmania) chagasi. Thirty-three dogs sacrificed at the Zoonosis Control Center of Araçatuba, a municipality endemic for visceral leishmaniasis (VL), were used. The animals were classified as asymptomatic, oligosymptomatic, and symptomatic groups. At the necropsy, bone marrow samples were collected from the femur, fixed, processed, and stained with hematoxylin and eosin. The lesion intensity was classified as mild, moderate, or severe. The parasite load was determined using immunohistochemistry. The most important lesions consisted of multifocal to diffuse granulomas, megakaryocytic dysplasia, and medullary aplasia. There were no statistical differences between the three clinical groups regarding parasite load and lesion intensity. Asymptomatic dogs also presented high parasitism in the bone marrow as dogs with clinical signs of VL. It was concluded that, regardless of clinical group, the bone marrow is a site for multiplication of Leishmania chagasi. Possibly, the bone marrow dysplasia may arise from the presence of many parasitized and activated macrophages in this organ. Consequently, it affects the profile of hematopoietic cells in the bone marrow and systemic circulation.